Determination of Route Suggestions Based on Flood Monitoring System: English - Zulkaflee, Farah Nabila; Ab Ghafar, Aimi Syamimi (Progress in Engineering Application and Technology, 2023)
Flooding is one of the catastrophic and frequently occurring natural disasters that cause extensive damage to life, infrastructure, and the environment. Floods are one of the common natural hazards in the Asian region. In addition, the massive flood caused many roads to be closed and caused the public to be strained. This incident has caused many vehicles to congest the rest and drive past congestion incidents. Water overflow from the floods that hit the area has caused road congestion too. Road congestion has caused many road users to be stranded, and some are willing to fight the current to avoid getting caught in this flood. Besides, many road users need to know which road to avoid getting caught in the downpour. In this project, a method to determine shortest route suggestion based on flood monitoring system is develop to overcome this problem. MATLAB software is used as the simulation tool to generate the route suggestion. The flood monitoring system data is extracted from Google Sheets. The system uses the data input to identify the best route for users to travel to their destination during the flooding period. The Directed Graph (DA) algorithm, finds the shortest path for all nodes by using the destination source and location obtained based on Google Maps. The shortest path data from MATLAB are saved to the Google Sheets, giving the directions in the most concise way for each node. Its main aim is to develop an intelligent system capable of routing people from one place to another to avoid the congestion caused by floods.